Identifying Major Actors of Shi’i Revival in Post-Soviet Azerbaijan - Göyüşov, Altay (Journal of religion in Europe, 2021)
This article is an attempt to describe, analyze, and evaluate the major players who contributed to the rise of transnational Shi’i activism in post-Soviet Azerbaijan. The article is based on a chronology of the most important events, and internet resources, personal contacts, observations, and interviews have been the primary source of this research.